Determinasi BOPO,LDR, dan NPL Terhadap ROA Perbankan Indonesia 2019-2023 - Wiwid Mufitasari; Lenni Yovita; Dian Prawitasari; Almira Santi Samasta (LPPM Politeknik Pratama, 2025)
This study was conducted to analyze the relationship between the financial ratios of BOPO, LDR, and NPL on Profitability (ROA) in banking companies listed on the IDX for the period 2019–2023. A quantitative approach was used with multiple linear regression analysis based on secondary data from the financial reports of 20 companies selected through purposive sampling. The results of the study show that BOPO and NPL have a significant negative effect on ROA, while LDR shows a positive but insignificant effect. These findings affirm that operational efficiency and credit quality play an important role in a bank's profitability, while LDR only serves as a positive signal when accompanied by good credit management. The results of this study are expected to serve as a reference in formulating policies to improve banking financial performance.